Best Proximity Point for Some Type of Cyclic Mappingin Strong ḇ-Metric Space - Ali, Walaa Fadel; Ahmad, Buthainah A.A (Iraqi Journal of Science, 2025)
The best proximity point generalization of fixed point that is beneficial when the contraction map is not a self-map. The aim of this paper is to introduce new types of proximal contraction for cyclic mapping in strong ḇ-metric space that. Let be complete strong ḇ-metric space and let be two nonempty closed subsets of . Take the cyclic mapping . If is satisfies following condition for all and , where then is Kannan cyclic, if is satisfies following condition for all and , where then is Ćirić cyclic, if is satisfies following condition for all and , where Meir-Keeler mapping then is Meir-Keeler -Kannan-Ghatterjee. The exi